Group Knowledge and Group Knowledge Processes in School Board Decision Making - Newton, Paul; Sackney, Larry (Canadian Journal of Education/Revue canadienne de l’éducation, 2005)
This study examined group knowledge in three school boards, which we conceptualised as a phenomenon influenced by structural/political and social/relational elements and composed of affective, axiological, and cognitive dimensions. Several data collection techniques were used: surveys, conversation analysis, observation, and the Critical Decision Method (CDM). Results indicate that group knowledge is strongly influenced by group communication patterns and the structural and political environment. Most importantly, the results suggests that the affective, axiological, and cognitive dimensions of group knowledge are not discrete, but interact with each other within the processes of knowledge transformation and knowledge transfer Key words: educational governance, decision‐making, emotion, cognition, values L’étude porte sur les connaissances du groupe au sein de trois conseils scolaires. D’après les auteurs, il s’agit d’un phénomène influencé par des éléments structurels/politiques et sociaux/relationnels et regroupant des dimensions affective, axiologique et cognitive. Plusieurs techniques de collecte de données ont été utilisées : sondages, analyse de conversations, observations et la Critical Decision Method (CDM). Les résultats indiquent que les connaissances du groupe sont fortement influencées par les méthodes de communication dans le groupe et le contexte structurel et politique. Ces résultats semblent surtout indiquer que les dimensions affective, axiologique et cognitive des connaissances du groupe ne sont pas discrètes, mais qu’elles s’influencent mutuellement au sein du processus de transformation et de transfert des connaissances. Mots clés : gouvernance en éducation, prise de décisions, émotion, cognition, valeurs.